2017
DOI: 10.1021/acschemneuro.7b00357
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Assessment of the Intranasal Delivery Route for Orexin A

Abstract: Intranasal drug delivery is a noninvasive drug delivery route that can enhance systemic delivery of therapeutics with poor oral bioavailability by exploiting the rich microvasculature within the nasal cavity. The intranasal delivery route has also been targeted as a method for improved brain uptake of neurotherapeutics, with a goal of harnessing putative, direct nose-to-brain pathways. Studies in rodents, nonhuman primates, and humans have pointed to the efficacy of intranasally delivered neurotherapeutics, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…of OXA significantly ameliorated motor and cognitive functions of rats with Parkinson's disease [46]. By using PET scan, Van de Bittner et al found that intranasal administration of OXA achieved similar drug concentration and biological effect compared with intravenous route [21]. Based on these studies, we thus postulated that OXA should have similar neuroprotective effect on mice with ICH and evaluated the effects of intranasal OXA delivery to study its effect in ICH.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…of OXA significantly ameliorated motor and cognitive functions of rats with Parkinson's disease [46]. By using PET scan, Van de Bittner et al found that intranasal administration of OXA achieved similar drug concentration and biological effect compared with intravenous route [21]. Based on these studies, we thus postulated that OXA should have similar neuroprotective effect on mice with ICH and evaluated the effects of intranasal OXA delivery to study its effect in ICH.…”
Section: Discussionmentioning
confidence: 82%
“…However, it will be important to study the effect of OXB in future studies. Furthermore, previous study by Van de Bittner et al found that intranasal administration of OXA was able to achieve similar drug concentration and biological effect compared with intravenous route using PET scan study [21]. Also, the study by Kastin et al demonstrated that OXA can cross the BBB [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological parameters such as the radiotracer molecule under investigation, target density within the brain, and level of permeability to the BBB are also important considerations. Previous work with the IN administration of 11 C ‐Orexin noticed no uptake in images after 90 min, however, they noticed low levels of %ID/cc in the olfactory cortex of ex‐vivo dissection of rodent brain, detailing that the minimum detectable threshold of the scanner may not have been reached for imaging purposes 35 . Of note from this work also is that IN administration can result in approximately 3–10 times lower brain exposure of the compound compared to IV administration of the same dose 35 …”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we posited that modulation of Orx 2 function would result in modification of adaptive emotional and defensive behavior in mice. As Orx has been shown to be functionally effective following intra-nasal delivery (Baier et al, 2008; Dhuria et al, 2009; Modi et al, 2017; Van de Bittner et al, 2018), a putatively systemic brain Orx 2 -induced anxiolysis could be of therapeutic value. We hypothesized that icv delivery of an Orx 2 agonist would promote resilience, result in a reversal of submissive behavior, and decrease anxious and depressive behaviors.…”
Section: Introductionmentioning
confidence: 99%